Analysis Performance of Hospital Based Criteria Malcolm Baldrige in RSUD dr. Iskak Tulungagung Post-Determination of Accreditation Level Plenary - Yulikha Rakhmawati (Journal for Quality in Public Health, 2018)
Criteria Malcolm Baldrige has a focus on superior performance for the entire organization in a managerial framework that is comprehensive, identify and track all the results of the organization that is the customer, product or service, finance, human resources and organizational effectiveness. The research objective is to analyze the performance of RSUD Dr. Iskak Tulungagung based on criteria Malcolm Baldrige post determination plenary level accreditation. The study design used in the study was cross-sectional. The population is all in addition to the Board of Directors Structural RSUD Dr. Iskak Tulungagung. The sample size was 44 respondents using technique. proportionate stratified random sampling Independent research variables are Leadership, Strategic Planning, Customer Focus or Patient, Measurement, Analysis and Knowledge Management, focus on human resources, focus on the process and results. Data was collected using a questionnaire, then the data were analyzed. The results showed that the majority of respondents have good leadership category as many as 40 respondents (90.9%), the Strategic Planning Category well as much as 42 respondents (95.5%), Customer Focus category patient good or as many as 41 respondents (93.2 %), Category Measurement, Analysis and Knowledge Management was good as much as 40 respondents (90.9%), Category Focus On Human Resource good as much as 34 respondents (77.3%), Category Focus On good process as many as 40 respondents ( 90.9%), research found criteria organizational criteria based on organizations the Baldrige assessment with 887.4 points as a Word Leader. Conclusion of the study was hospital has a good performance and criteria for the organization based on the Baldrige assessment as Word Leader.